Pengaruh Profitabilitas, Leverage, Kualitas Good Corporate Governance dan Jenis Industri Terhadap Manajemen Laba(Studi Empiris Pada Perusahaan Go Publik Yang TerdaftarDalam Penilaian CGPI Pada Tahun 2010-2013) - Putro, Rengga Ganang Anggoro; , Dr. Triyono, SE., M.Si (2016)
This aim of this research examines influence of profitability, leverage, good corporate governance quality and industry type to earnings management. The objects of study are all of go public companies are include in CGPI period 2010-2013. The study used purposive sampling method to collect the sample. The number of samples were of 70 data. Testing the hypothesis in this study used multiple regression. The results showed that the Profitability (ROA) and Industry Type (JI) have effect on Earnings Management, while the Leverage (LEV) and Good Corporate Governance Quality (KGCG) has not effect on Earnings Management.